The three ages of women: an analysis of dystopian portrayals of women and motherhood in the handmaid’s tale (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
Women’s identity, as feminist studies have shown, is a cultural and social construction that is closely related to motherhood. Since the media have a central role in the social construction of reality, analyzing a series such as The Handmaid’s Tale, focused on women, motherhood and (in)fertility, can shed light on the models of femininity and motherhood present in our own society. Through a qualitative methodology, the first season of the series is analyzed, focusing on the representation of women, the female body and motherhood. The television text allows us to reflect on three aspects in particular: the interconnections between fiction and reality, the misogyny in the female gaze itself, and the stigma of infertility.
Keywords: gender; motherhood; media representations; TV series; women